39.7k views
5 votes
If 3x + y = k (x-3), then x =

2 Answers

5 votes
Move all terms to the left side and set equal to zero. then set each factor equal to zero
X =
(3k+y)/(k-3)
User Ebyhr
by
6.6k points
5 votes

The above answer will be calculated as -

This is a linear equation in more than one variable. We will convert the equation for the value of x.

We will shift all the other variables other side, except x.

Given,

3x + y = k ( x -3)

3x + y = kx - 3k

3x - kx = - 3k - y

x (3 - k) = - (y + 3k)

x =
(- (y + 3k))/(- ( k -3))

x =
( (y + 3k))/( ( k -3))

Thus, the value of x has been calculated.

User Sergey Vasiliev
by
5.8k points